The qualitative approach and the renewal of school geography supported by pedagogical positivism - Santiago Rivera, José Armando (2020)
The article analyzes the qualitative approach as an option to renew the school geography based on pedagogical positivism. Since the 19th century, geographical teaching has been facilitated with the purpose of transmitting contents related to the physical-natural features of the territory, from the descriptive, reproductive and memoristic perspective. This educational reality is an epistemic obstacle, as it prevents the analytical reflection of community geographic situations and the era from being developed. Methodologically, literature was reviewed and a historical explanation of school geography from the positivist foundations and positivism to qualitative science in geographical teaching was presented. It concludes by proposing that in the school geography it is relevant to assume the opinion originated in the community’s performance of the inhabitant, in the study of the themes and problems identified in their area. It brings the importance of the testimonies of the inhabitants of the community to enable the formation of critical awareness as a formative mission of school geography.